New strategies for the synthesis of alpha-amino acetals and their applications in the synthesis of dihydro-methano-diarylazocines and dopamine D1 receptor ligands - Tian, JieSheng (2012)
This thesis consists of five chapters and an appendix. It is primarily about new strategies for the synthesis of alpha-amino acetals and their applications in the synthesis of dihydro-methano-diarylazocines and dopamine D1 receptor ligands.